Operations management model for automotive service workshops in Peru: service level improvement through lean manufacturing and SLP - Miranda Bazan, Ximena Fiorella (2025)
[The automotive repair SME sector in Latin America faces persistent operational challenges that hinder its efficiency and competitiveness. Prior studies have explored Lean methodologies and Systematic Layout Planning (SLP) in large-scale industries, leaving a gap in the adaptation of these tools for smaller automotive workshops. The discrepancies above are sought to be solved through the formulation and verification of an integrated operations management model which combines the Lean Manufacturing approach and SLP. It concentrated on the application of 5S technique, layout optimization, and process standardization to minimize movements and delays. The verification step showed substantial improvement of the service level from 84.91% to 95.00% along with 32.99% improvement in the diagnostic time. These results demonstrate that the model has capacity to enhance service quality and operational efficiency and contribute to the academic literature and practice by providing a model that is usable by SMEs. Further research should assess the sustainability of the model and the use of digital monitoring systems].